2022
DOI: 10.1038/s41598-022-05482-7
|View full text |Cite
|
Sign up to set email alerts
|

Did border closures slow SARS-CoV-2?

Abstract: Despite the economic, social, and humanitarian costs of border closures, more than 1000 new international border closures were introduced in response to the 2020–2021 pandemic by nearly every country in the world. The objective of this study was to examine whether these border closures reduced the spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Prior to 2020, the impacts of border closures on disease spread were largely unknown, and their use as a pandemic policy was advised against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 28 publications
1
29
2
1
Order By: Relevance
“… 109 However, a 2022 study found no evidence that border closures reduced the spread of COVID-19. 110 Border measures can work only if they are timely, comprehensive, and complemented by policies to suppress local outbreaks that will continue to occur even with comprehensive travel measures.…”
Section: Section 2: a Review Of The Global Regional And National Resp...mentioning
confidence: 99%
“… 109 However, a 2022 study found no evidence that border closures reduced the spread of COVID-19. 110 Border measures can work only if they are timely, comprehensive, and complemented by policies to suppress local outbreaks that will continue to occur even with comprehensive travel measures.…”
Section: Section 2: a Review Of The Global Regional And National Resp...mentioning
confidence: 99%
“…Many authors tried to assess the effectiveness of different non-pharmaceutical interventions (NPIs). The authors of [ 19 , 109 – 111 ] also partially focused on economic development and provided evidence for the effectiveness of lockdowns. The authors of [ 112 , 113 ] derived confidence intervals for the effect of fine-grained NPIs such as school or workplace closures or gathering bans based on data for 149 and 41 countries, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…While this is intuitively appealing, its utility and practicality in a real-world scenario remains yet to be demonstrated. Recently, the authors of [ 111 ] found evidence in favor of domestic lockdowns to reduce the spread of the disease. On the other hand, the authors could not find any results in favor of border closures such that alternative strategies need to be found.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors tried to assess the effectiveness of different non-pharmaceutical interventions (NPIs). The authors of [109, 110, 111, 19] also partially focused on economic development and provided evidence for the effectiveness of lockdowns. The authors of [112, 113] derived confidence intervals for the effect of fine-grained NPIs such as school or workplace closures or gathering bans based on data for 149 and 41 countries, respectively.…”
Section: Discussionmentioning
confidence: 99%